English - Spasić, Igors; Ubavić, Milan; Šumarac, Zorica; Todorović, Maša; Vučković, Biljana (Journal of Medical Biochemistry, 2020)
AbstractAim: To investigate influence of lipid metabolism disorders on the risk of deep vein thrombosis.Methods: A total of 200 subjects participated in the study, 100 of whom experienced DVT with or without PTE, and 100 healthy subjects representing the control group. We classified patients and controls in terms of serum concentrations of chylomicrons, LDL, IDL, VLDL and HDL particles, as those with or without hyperlipoproteinemia and in terms of serum Lp(a) lipoprotein levels, as those with hyperLp(a) lipoproteinemia (serum Lp(a) values> 0.3g /l) and those without hyperLp(a) lipoproteinemia (serum Lp (a) values ​​
Keywords: English